Severe supracondylar lysis of the third metatarsal bone due to intra‐articular haemorrhage with similarities to human pigmented villonodular synovitis: A differential diagnosis to intra‐articular neoplasia. (27th August 2013) - Hinnigan, G. J.; Papoula‐Pereira, R.; Hetzel, U.; Singer, E. R.
Summary: This report describes a case of severe supracondylar lysis of the third metatarsal bone of a mature Cob gelding. The gelding presented with moderate to severe lameness and soft tissue swelling in the distal metatarsal region. A mass was present plantar to the third metatarsal bone and dorsal to the suspensory ligament branches. The mass was removed surgically, and was found to be a large blood coagulum within an enlargement of the plantar pouch of the metatarsophalangeal joint. The mass was pedunculated and attached to a region of abnormal synovium. This synovium was identified histologically as being an area of villonodular synovitis. The lesion had similarities with human pigmented villonodular synovitis. Removal of the abnormal tissue resulted in resolution of the lameness and of the lysis of the third metatarsal bone. Haemarthrosis should be considered in the list of differential diagnoses for focally mineralised soft tissue masses found within an articulation, and may be associated with pigmented villonodular synovitis.